Economic Losses of Condemned Livers and Lungs due to Infectio with Common Reportable Diseases of Slaughtered Ruminants at Kerbala Abattoirs - Al-Nassir, Hikmat Sahib (Journal of Kerbala for Agricultural Sciences, 2017)
A study was carried out at kerbala slaughterhouses during 6 month-period from October 2015 to March 2016 in order to estimate the economic losses of condemned livers and lungs of slaughtered ruminants due to common reportable diseases. Diagnosis of diseases and lesions of livers and lungs depended on pathological changes of organ, color, size, consistency, presence of parasites and lesions. Out of 67,500 heads of slaughtered sheep, goats, cattle, and buffaloes which were slaughtered during this study at Kerbala abattoirs, condemnation of livers and lungs was carried out in 2002 (2.96%) of the slaughtered animals, of which 22 (0.03%) , 15 (0.02%) , 302 (0.45%) , 91 (0.13%) of the slaughtered animals were due to hydatidosis, facioliasis , lung worms, pneumonia and hepatitis respectively. The highest infection rate of the condemned livers in slaughtered ruminants was recorded due to hydatidosis 1,324(1.96%), followed by hepatitis 91(0.13%) and fascioliasis 22(0.03%). The livers of 1.32% sheep, 7.42% goat, 3.36% cattle and 4.06% buffaloes carried hydatid cysts, and the infection rate of hydatidosis in livers of goats was significantly higher than other animal species with ( P< 0.05 ). However, lungs of slaughtered ruminants were frequently disposed due to hydatid cyst (1.004%) ,followed by pneumonia (0.45%) and lung worms (0.02%), and that lungs of goats (3.72%) were condemned more frequently with a significant difference ( P <0.05) than other animal spp. The findings of the current study revealed that condemnation of livers and lungs of sheep, goat, cattle and buffaloes in kerbala abattoirs due to parasitic infestation and other pathological lesions caused considerable economic losses. The estimated total losses due to condemned livers and lungs in buffaloes and cattle were (28,250,000 Iraqi Dinars ,ID) (21,730 ) but in sheep and goats ,the losses were (46,650,000 ID) (35,884 ) and the total economic losses recorded in this period of study for all species of animals slaughtered in abattoirs due to condemned lungs and livers were (74,900,000 ID) (57,615 ) .